Behandlung der Nasenatmungsbehinderung bei Patienten mit obstruktiver Schlafapnoe = Treating nasal obstruction in obstructive sleep apnea patients - Verse, Thomas; Wenzel, Stefan (HNO, 2017)
The impact of treating nasal obstruction in obstructive sleep apnea (OSA) patients is still intensively discussed at congresses. This is likely due to the highly conflicting results of nasal treatments in regard to restorative sleep on the one hand, and their influence on the severity of OSA on the other. Both conservative and surgical nasal treatments result in a highly significant improvement of sleep quality. Patients’ sleep is more restorative, which has a huge impact on several quality of life parameters. In contrast, the impact of conservative and surgical nasal treatments on the severity of OSA measured using the apnea-hypopnea index is very limited, apart from rare exceptions. However, there are preliminary data indicating that successful nasal surgery may facilitate or enable nasal ventilation therapy by lowering the effective pressure.